Rheological modifications of the asphalt-polymer system using microwave technology - Rand Matti; Khalid Owaid (College of Education for Pure Sciences, 2020)
This research aimed to prepare different types of asphaltic materials having a good rheological properties compared with the non-modified asphaltic materials. Different polymers and microwaves were used to prepare the modified asphalt in different ways. The first method is based on the modification of asphalt with reclaim tire rubber using anhydrous aluminum chloride catalyst at 360 watt at different times, The second method depends on the same principle of the first method with the introduction of sulfur as an additive and the third method is based on the same principle of the first method but the change of polymer added to the polyamethyl methacrylate and with the introduction of sulfur as an additive. The latter method is the same principle of the first method but the change of polymer added to mixtures of (1:1)(polymer_polymer)(recycled tire rubber polyamethyl methacrylate)with the introduction of sulfur as an additive. The above methods we obtained asphaltic materials which can be used in paving and mastic depending on the measured (ductility, penetration , softening point).